2012
DOI: 10.1634/theoncologist.2012-0079
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Retrospective Study of 132 Patients with Unresectable Small Bowel Adenocarcinoma Treated with Chemotherapy

Abstract: Background. No standard chemotherapy regimen has been established for unresectable or recurrent small bowel adenocarcinoma (SBA).Methods. Clinical courses of 132 patients with unresectable or recurrent SBA who received chemotherapy at 41 institutions in Japan were reviewed retrospectively. Patients were classified into five groups according to first-line chemotherapy regimens: fluoropyrimidine monotherapy (group A), fluoropyrimidine-cisplatin (group B), fluoropyrimidine-oxaliplatin (group C), fluoropyrimidine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 33 publications
4
63
0
Order By: Relevance
“…These findings are in line with the observation of Tsushima et al [16]. The location of the primary tumor may also affect prognosis.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in line with the observation of Tsushima et al [16]. The location of the primary tumor may also affect prognosis.…”
supporting
confidence: 92%
“…Tsushima et al [16] are to be commended for performing such a study. In their retrospective multicenter study, the survival of patients with advanced SBA receiving first-line therapy was compared among five different treatment groups.…”
mentioning
confidence: 99%
“…SBA is more similar to colorectal cancer than gastric cancer based on genome-wide DNA copy number aberrations (14); therefore, chemotherapy regimens used to treat colorectal cancer are typically selected for the treatment of SBA. Previous retrospective studies have demonstrated that chemotherapy, including oxaliplatin with fluorouracil and folinic acid (FOLFOX) chemotherapy, and oxaliplatin and capecitabine (CAPOX) chemotherapy, contributes to a longer survival time in patients with SBA (15)(16)(17)(18)(19). The overall survival (OS) time of patients who received chemotherapy was 15.1-22.2 months (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Several phase II studies examining a variety of protocols with different OS have been published [21][22][23][24][25]. There are also retrospective single centre experiences comparing different regimens [5,15,16,20,[26][27][28][29][30]. Current expert opinion favors use of a fluoropyrimidine-platinum combination in the first line [20,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…There are also retrospective single centre experiences comparing different regimens [5,15,16,20,[26][27][28][29][30]. Current expert opinion favors use of a fluoropyrimidine-platinum combination in the first line [20,26,27]. However, definitive data for treatment selection are lacking.…”
Section: Discussionmentioning
confidence: 99%